Survey on Nursing Home Caregivers' Basic Knowledge of Oral Health Management: Dental Terminology - Shizuko Yanagisawa; Masami Yoshioka; Yasuhiko Shirayama (MDPI AG, 2018)
With the increasing numbers of the elderly requiring care in Japan, the management of their oral health care will require cooperation between medical and dental professionals, and we need to transfer dental knowledge from dental professionals to caregivers. With the help of a questionnaire, we examined 181 caregivers’ depth of understanding regarding 20 typical dental terms with a view to improving the educational instruction provided to them. It was found that except for “clasp”, popular dental terms have largely been accepted. The differences in their degrees of understanding could be owing to the lack of systematic education for caregivers.